Advantages of magnifying narrow‐band imaging for diagnosing colorectal cancer coexisting with sessile serrated adenoma/polyp. (17th April 2016) - Chino, Akiko; Osumi, Hiroki; Kishihara, Teruhito; Morishige, Kenjiro; Ishikawa, Hirotaka; Tamegai, Yoshiro; Igarashi, Masahiro
Abstract : Background and Aim: In the present study, we investigated the advantages of narrow‐band imaging (NBI) for efficient diagnosis of sessile serrated adenoma/polyp (SSA/P). The main objective of this study was to analyze the characteristic features of cancer coexisting with serrated lesion by carrying out NBI. Methods: We evaluated 264 non‐malignant serrated lesions by using three modalities (conventional white light colonoscopy, magnifying chromoendoscopy, and magnifying NBI). Of the evaluated cancer cases with serrated lesions, 37 fulfilled the inclusion criteria. Results: In diagnosing non‐malignant SSA/P, an expanded crypt opening (ECO) under magnifying NBI is a useful sign. One hundred and twenty‐five lesions (87%) of observed ECO were, at the same time, detected to have type II open pit pattern, which is known to be a valuable indicator when using magnifying chromoendoscopy. ECO had high sensitivity of 80% for identifying SSA/P, with 62% specificity and 83% positive predictive value (PPV). In detecting the cancer with SSA/P, irregular vessels under magnifying NBI were frequently observed with 100% sensitivity and 99% specificity, 86% PPV and 100% negative predictive value. Conclusions: A focus on irregular vessels in serrated lesions might be useful for identification of cancer with SSA/P. This is an advantage of carrying out magnifying NBI in addition to being used simultaneously with other modalities by switching, and observations can be made by using wash‐in water alone. We can carry out advanced examinations for selected lesions with irregular vessels. To confirm cancerous demarcation and invasion depth, a combination of all three aforementioned modalities should be done.